miR-142 favors naïve B cell residence in peripheral lymph nodes - Hagen, Magdalena; Chakraborty, Tirtha; Olson, William J.; Heitz, Martin; Hermann-Kleiter, Natascha; Kimpel, Janine; Jenewein, Brigitte; Pertoll, Johanna; Labi, Verena; Rajewsky, Klaus; Derudder, Emmanuel (Frontiers in Immunology, 2022)
B lymphocyte development proceeds through a well-ordered sequence of steps, leading to the formation of a sizeable mature B population recognizing a diversity of antigens. These latter cells are ultimately responsible for the production of antibodies upon immune challenges. The detection of threats to the organism is facilitated by the ability of naïve follicular B cells, the main subset of mature B cells in mice, to circulate between lymphoid tissues in search of their cognate antigens. miRNA-mediated fine-tuning of mRNA stability and translation participates in the optimal expression of genetic programs. This regulatory mechanism has been shown to contribute to B cell biology, although the role of individual miRNAs remains understudied. Here, we selectively inactivated the miR-142 locus in B cells. As a consequence, the mature B compartment was visibly perturbed, in agreement with work in miR-142 knockout mice. However, our strategy allowed us to identify roles for the miR-142 locus in B cell physiology obscured by the complexity of the immune phenotype in the null mutant mice. Thus, these miRNAs are necessary for the proper formation of the pre-B cell compartment during development. More remarkably, naïve follicular B cells demonstrated altered migratory properties upon conditional inactivation of the miR-142 locus. The latter mutant cells expressed reduced levels of the homing molecule CD62L. They also migrated more efficiently towards sphingosine-1-phosphate in vitro and displayed an increased abundance of the sphingosine-1-phosphate receptor 1, compatible with improved lymphocyte egress in vivo. In line with these observations, the ablation of the miR-142 locus in B cells caused a paucity of B cells in the lymph nodes. Mutant B cell accumulation in the latter tissues was also compromised upon transfer into a wild-type environment. These changes coincided with suboptimal levels of FOXO1, a positive regulator of CD62L transcription, in mutant B cells. Overall, our findings indicate contributions for the miR-142 locus in various aspects of the B cell life cycle. Notably, this locus appears to favor the establishment of the migratory behavior required for naïve follicular B cell patrolling activity.